Restoration of tropical forest ecosystems: proceedings of the symposium held on October 7-10, 1991 - Lieth, Helmut (Springer, 1993)
The destruction of the tropical forests continues rapidly. We all know that this has global, ecological and economic consequences. The problem is of such magnitude that it can only be compared to warfare. The destruction of tropical forests is both detrimental to the global ecology as well as posing a serious threat to the people living in these areas. Furthermore, the overutilization of such a valuable resource poses a serious threat to the next generations. Besides the problem generated for the people in these regions, and for the earth in general, there is a moral obligation to preserve the vast biological diversity in the tropical forests. We have a commitment to all species on earth as well as man and, therefore, need to preserve as many as possible, if not all. This book discusses the problem from different angles: from forestry, ecology and nature conservation. The two main problem areas are: first the wise utilization of that portion of the forest which will be used - especially the introduction of planned forestry in such areas and second the development of a good plan for nature conservation in the tropics
Keywords: Konferenzschrift